Match-Play Running Demands and Technical Performance Among Elite Gaelic Footballers: Does Divisional Status Count?. Issue 1 (January 2021) - McGahan, Jason H.; Mangan, Shane; Collins, Kieran; Burns, Con; Gabbett, Tim; O'Neill, Cian
Abstract : Abstract: McGahan, JH, Mangan, S, Collins, K, Burns, C, Gabbett, T, and O'Neill, C. Match-play running demands and technical performance among elite Gaelic footballers: Does divisional status count? J Strength Cond Res 35(1): 169–175, 2021—The aim of the current study was to compare positional differences in running demands and technical performance variables among elite Gaelic football teams from separate divisions. Data were obtained from a division 1 (26.7 ± 2.9 years, 179.2 ± 21.3 cm, 89.9 ± 21.2 kg) and a division 3 (25.7 ± 3.5 years, 183.0 ± 4.7 cm, 84.4 ± 6.5 kg) team. Match-play running variables were collected using 4-Hz global positioning system (GPS) units (VX Sport; Visuallex Sport, Lower Hutt, New Zealand) (Match data sets; division 1: n = 107, division 3: n = 97). Selected variables assessed were high-speed running distance (HSR) (≥17 km·h −1 ), number of high-speed efforts (HSE) (≥17 km·h −1 ), relative high-speed distance (RHSD) (≥17 km·h −1 ; m·min −1 ), and percentage of time at high speed (%HS). Each variable was analyzed across the 5 positional groups in Gaelic football (full back, half back, midfield, half forward, full forward). The same 25 competitive games were analyzed using the GPS and the Sports Code video analysis system (Sports Code Elite V9; Sportstec, Warriewood, NSW, Australia). Technical performance variables selected for analysis were total kick/hand passes, tackles, shots, and percentage of time in possession. High-speed running distance running demands were differentiated between the divisions; the division 3 team demonstrated significantly greater HSR, HSE, RHSD, and %HS than the division 1 team ( p ⩽ 0.05). Positional-specific analysis found that the division 3 full back and midfield positional lines had significantly greater HSR, RHSD, and %HS than their division 1 counterparts. The division 1 team made a greater number of total tackles, with significantly more tackles in the middle third ( p ⩽ 0.05). The division 3 team performed a significantly greater number of hand passes and unsuccessful shots per game ( p < 0.01). The results of this study indicate that overall technical proficiency, rather than high-speed running profiles, differentiate division 1 and 3 Gaelic football teams.